Harmonizing Wisdom: Exploring the Synchronicity of Taoism and Maitreya Buddhism in Indonesia's Pluralistic Tapestry - Indah Ayu Pratiwi (Subhasita: Journal of Buddhist and Religious Studies, 2023)
This article aims to explore the parallels between Taoism and Maitreya Buddhism, focusing on their teachings of wisdom. To achieve this, qualitative research methods such as interviews, observation, and documentation were employed for data collection. The research findings showcase the inheritance of beliefs and practices from the White Lotus sect within Maitreya Buddhism, a sect deeply influenced by Taoist teachings. The syncretism of Taoist beliefs within Maitreya Buddhism is evident through the existence of the White Lotus sectarian influence. Moreover, this study unveils shared historical beliefs that serve as a spiritual link between humans, Earth, and heaven. Both Taoism and Maitreya Buddhism emphasize the importance of truth teachings in connecting these realms. Additionally, the convergence between the two traditions lies in their belief systems centered on moral ethics for creation and salvation. Maitreya Buddhism recognizes the future coming of Maitreya Buddha, who will descend to Earth to save humanity from the negative impact of misguided teachings, while Taoism also acknowledges the Enlightening Teacher. This research offers valuable insights into the intertwining of Taoism and Maitreya Buddhism in the diverse religious landscape of Indonesia. The parallels found in their teachings of wisdom and shared beliefs provide a deeper appreciation of the spiritual interconnectedness in this pluralistic society.